(4x - 3)(16x^2 + 12x + 9)
It is: -3(4x-0.50) = -12x+1.50 or as 1.50-12x
The expression can be factored as -12x + 32y -16z = 4(-3x + 8y - 4z) but a slightly improved presentation would be to extract -4 from the original expression. So, -12x + 32y -16z = -4(3x - 8y + 4z)
GCF = 12x.24x = 2(12x)36x3 = 3x2(12x)
The answer will depend on what x9 is equal to..
x9/x2 = x9-2 = x7
The answer will depend on the expression - which is not given!
The given expression can be simplified to -12x-2
3x(12x-2) is equivalent to 36x^2 -6x simplified
22
22
12x + 5 - 2x =(12x - 2x) + 5 =10x + 5 =5 (2x + 1)
If you mean: x2+12x+35 then it is a quadratic expression that can be factored as: (x+5)(x+7)
If you mean x^2 -12x+35 then it is a quadratic expression which can be factored in the form of (x-7)(x-5)
17
30+12x = 6(5+2x)
(4x - 3)(16x^2 + 12x + 9)